2020
DOI: 10.31557/apjcp.2020.21.8.2265
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in Exon2 of BRCA1 Gene in Adult Bengali Bangladeshi Female Patients with Breast Cancer: An Experience from Two Tertiary-Care Hospitals

Abstract: Breast cancer is the most common cancer of women worldwide. The Global Cancer Project provides evidence that 20,88,849 (11.6% of all cancers) new cases of breast cancer were identified around the world in the year 2018 and 6,26,679 deaths (6.6% of all cancer deaths) occurred in the same year (Globocan, 2018). It is predicted that the new cases of breast cancer patients will reach up to 22 million in next two decades (Ghoncheh et al., 2016). Like Western countries, it is now growing strongly in Asia and has bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A total of 5 mutations 48TtoG, 67GtoC and 75CtoA in exon 2 of BRCA1 were identified in Bangladesh. 8 And in another study, 3 novel mutations were found in a patient, 2/3 mutant sequences had effect on amino acid coding. 20 In Nepalese, The prevalence of 185delAG in breast cancer patients was found to be 8% but 1294del40 was not appeared.…”
Section: Figure1: the Average Age Of Patients With Breast Cancer From...mentioning
confidence: 94%
See 2 more Smart Citations
“…A total of 5 mutations 48TtoG, 67GtoC and 75CtoA in exon 2 of BRCA1 were identified in Bangladesh. 8 And in another study, 3 novel mutations were found in a patient, 2/3 mutant sequences had effect on amino acid coding. 20 In Nepalese, The prevalence of 185delAG in breast cancer patients was found to be 8% but 1294del40 was not appeared.…”
Section: Figure1: the Average Age Of Patients With Breast Cancer From...mentioning
confidence: 94%
“…27 National Institute of Cancer Research and Hospital of Bangladesh reported that the average age among breast cancer patients was 41.8. 8 In Nepalian study, the mean age of onset breast cancer was 42.59. 5 Figure1 shows the average age determined from selected studies of Pakistan, India, Sri Lanka, Bangladesh and Nepal.…”
Section: Introduction Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The BRCA1 exon 2 and 20 were amplified in a final volume of 50 µL containing: 50 ng genomic DNA, 25 µL OneTaq Quick-load 2X Master Mix with Standard Buffer (NEB), and 1 µL of 10 µM each forward and reverse primer. The primers for the c.68_69delAG in exon 2 and the c.5266dupC in exon 20 mutations were adopted from Chowdhury et al (2020) and Mahfoudh et al (2019), respectively, and are given in Table 1. The primers for both exons were designed to anneal within the exon-intron boundaries of both 5' and 3' ends.…”
Section: Amplification and Gel Electrophoresismentioning
confidence: 99%